176 - CHARACTERIZATION OF CHRONIC RENAL PATIENTS IN HEMODIALYTIC TREATMENT IN A PRIVATE CLINIC EM NATAL / RN (Fiep Bulletin - online, 2011)
This exploratory, descriptive and quantitative study in a private clinic convening with the Sistema único de Saúde (SUS) in Natal / RN, in order to characterize patients with CRF on hemodialysis. The research was initiated after approval by the Ethics in Research (n.68/2008). Data collection was performed by consulting the records of the dialysis unit available in electronic medical records and then stored in a spreadsheet in Excel. The sample was composed of 173 medical records of patients with chronic renal failure on hemodialysis in clinic with dialysis time longer than 24 months. The data were categorized and processed using Microsoft-Excel XP and SPSS. The results of this study showed a population predominantly male (55.7%), with ages ranging from 18 to 59 years (64.4%), married (53.8%), with incomplete primary education (27.2% ); on dialysis for hypertensive nephrosclerosis (39.3%), with an average of 73.8 months of treatment time. It was found that females exhibit greater treatment time (between 76 and 216 months), this value being significant (p-value = 0.044). It was found that CRF is a chronic, stressful, which causes changes in lifestyle carrier. In this sense, it is for nurses offer patients the necessary means for develop mechanisms to cope with the illness in order to improve their living conditions and encourage the family to participate actively in the process.
Keywords: Insuficiencia Renal Crónica; diálisis renal; enfermería